Development of reference intervals for serum biochemistry in female Hanwoo cattle with different reproductive status - Sung-Ho Kim; Tae-Gyun Kim; Sang-Yup Lee; Saet-Byul Kim; Young-Bum Son; Seung-Joon Kim; Won-Jae Lee (Journal of Animal Reproduction and Biotechnology)
Background: Hanwoo cattle, an indigenous Korean breed, have become economically significant due to genetic improvements and large-scale farming. As individual cow value increases, understanding their unique physiology across different life stages is crucial for optimal health management. This retrospective study aimed to investigate serum biochemistry differences among non-pregnant, pregnant, and fattening female Hanwoo cattle and establish breed-specific reference intervals (RIs) for accurate health assessment, utilizing data obtained from routine veterinary care. Methods: Blood samples were collected from female Hanwoo cattle, categorized as pregnant (n = 12), non-pregnant (n = 25), and fattening (n = 11). Eighteen serum biochemical parameters were analyzed and descriptive statistics were calculated for each group. The new RIs in different reproductive status of female Hanwoo were established using the Reference Value Advisor program. Results: Significant differences based on reproductive status were identified in blood urea nitrogen (BUN), γ-glutamyl transferase (GGT), triglyceride (TG), glucose (GLU), and creatinine (CRE) levels. BUN, GGT, and TG levels were significantly higher in fattening cattle compared to pregnant and non-pregnant cows. GLU levels increased progressively across pregnant, non-pregnant, and fattening groups, while CRE levels were significantly higher in pregnant cows. Based on values of biochemical parameters, new RI were suggested for sixteen biochemical parameters, encompassing all three reproductive stages. Conclusions: This study established new RIs for female Hanwoo cattle across nonpregnant, pregnant, and fattening stages, providing a more accurate basis for health assessment and management. These findings will contribute to improved individual cow management, supporting genetic improvement efforts, and enhancing overall herd health in female Hanwoo cattle.